The Tortricidae described by J. C. Fabricius (Lepidoptera) - Baixeras, Joaquín; Karsholt, Ole (Zootaxa, 2011)
The identity and nomenclature of the 88 species of Tortricidae (Lepidoptera) described by J. C. Fabricius are reviewed. Type material deposited in the Natural History Museum Denmark is illustrated. Lectotypes for Tinea compositella (Fabricius, 1775), Pyralis rivellana (Fabricius, 1775) and P. strigana (Fabricius, 1775) are designated. Two new synonymies are proposed: Pyralis marmorana (Fabricius, 1798), syn. n., of Ancylis achatana (Denis and Schiffermüller, 1775), and P. rusticana (Fabricius, 1794), syn. n., of Epinotia solandriana (Linnaeus, 1758). In an appendix, the identity and nomenclature of the 49 species of non-Tortricidae described by Fabricius in the genus Pyralis Linnaeus, 1758 are reviewed. According to provisions of Article 23.9 of the International Code of Zoological Nomenclature, suppression of priority of Pyralis obscurana Fabricius, 1798 over Eucosma aspidiscana (Hübner, 1817), Pyralis posticana Fabricius, 1794 over Clepsis spectrana (Treitschke, 1830) and Pyralis trifasciana Fabricius, 1794 over Isotrias rectifasciana (Haworth 1811) is proposed. Appendices with references on the prevailing use of these three junior synonyms are included.